THE ANALYSIS OF PREPOSITION IN AND THEIR TRANSLATION IN INDONESIAN FOUND IN â€œREVENGE OF SEVENâ€ - Swarniti Ni Wayan; Yudi Sudarmawan I Putu; Dedik Susila I Komang (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
This paper focuses on the discussion of the forms of preposition in, the functions of preposition in and their translation in Indonesian. In this research, the theories used are the theory of grammar by Quirk (1973) in the book entitled A University Grammar of English and the theory of translation by Larson (1984) in the book entitled Meaning Based of Translation. For supporting theory, it was used the theory of preposition by Murthy (2003) in the book entitled Contemporary English Grammar for Scholar and Student. The data of this research were taken from the sentences that has preposition in in a novel entitled â€œThe Revenge of Sevenâ€ by Pittacus Lore and their translation in its Indonesian version in the same title that was translated by Nur Aini. After the data were collected by underlining the sentences which are related with the topic discussed, they were classified and analyzed based on the forms or preposition in, the functions of preposition in and their translation in Indonesian. Then, the results of the analysis were presented descriptively. Based on the analysis, the forms of preposition in are as single preposition, phrase preposition and prepositional phrase. The functions of preposition in found are for indicating place and time. Preposition in was translated into target language (TL) as di, ke, dalam, pada, selama, dari, and some of preposition in were not translated. Keywords: preposition, grammar, translation